2021
DOI: 10.1002/admt.202100170
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene Flanked Diketopyrrolopyrrole: A New Functional Dye Based Optical Sensors for Monitoring Cyanide Ions in Water

Abstract: Cyanide (CN−) is one of the most hazardous ions to humans and the environment. Therefore, sensitive, and selective sensors for CN− monitoring are highly required. A novel chemosensor based on naphthalene flanked diketopyrrolopyrrole dye (TBC‐DPPN) is synthesized for the direct detection of CN− in water samples by naked eye and vibrational spectroscopy (UV–Vis and fluorescence). The electron deficient carbonyl group of the lactam ring of TBC‐DPPN undergoes a nucleophilic attack by the CN− thus causing the yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Literature search revealed that diketopyrrolopyrrole (DPP) has been extensively studied as a sensor for different analytes such as cations, anions, reactive oxygen species, pH, CO 2 , and H 2 S gas . Gholami et al reported recognition of CN – ions in water using naphthalene-flanked DPP as an optical sensor . Recently, DPP derivatives have been examined as biosensors in live-cell imaging. ,, To our surprise, very few reports are available in the literature for explosive sensors based on DPP .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature search revealed that diketopyrrolopyrrole (DPP) has been extensively studied as a sensor for different analytes such as cations, anions, reactive oxygen species, pH, CO 2 , and H 2 S gas . Gholami et al reported recognition of CN – ions in water using naphthalene-flanked DPP as an optical sensor . Recently, DPP derivatives have been examined as biosensors in live-cell imaging. ,, To our surprise, very few reports are available in the literature for explosive sensors based on DPP .…”
Section: Introductionmentioning
confidence: 99%
“…21 Gholami et al reported recognition of CN − ions in water using naphthalene-flanked DPP as an optical sensor. 22 Recently, DPP derivatives have been examined as biosensors in live-cell imaging. 21,23,24 To our surprise, very few reports are available in the literature for explosive sensors based on DPP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of diketopyrrolopyrrole (DPP) derivatives as fluorescent probes has been extensively explored in the last decade due to their high fluorescence quantum yields, exceptional photostability, and moderately high molar absorption coefficients [ 1 , 2 , 3 ]. The focus of these applications has been the tracing of biologically and environmentally important species, namely cations and anions [ 4 , 5 , 6 , 7 ]. The chemical versatility of the DPP skeletal unit allows for different functionalization to create a diverse range of DPP-based multifunctional dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches for sensing cyanide ions have been reported in the literature. The nucleophilicity of the anion to attack carbonyl carbon, [21][22][23] alkenes [24][25][26] and playing around with proton abstraction are well documented. [27] However, the poor solubility of most organic ligands and the solvation of the cyanide ions in an aqueous medium limits the development of cyanide sensing.…”
Section: Introductionmentioning
confidence: 99%